2011
DOI: 10.1111/j.1477-2574.2011.00303.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of DNA methylation in hepatocellular carcinoma

Abstract: Epigenetic changes and profiles may correlate to the biological behaviour of tumours and clinical outcome of HCC patients. The use of DNA methylation profiles as a surrogate biomarker remains an active area of clinical cancer research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 61 publications
0
37
0
Order By: Relevance
“…DNMT3A seems to be the prominent responsible for the methylation of TTP promoter [45]. HCC tumors exhibit specific DNA methylation signatures associated with risk factors, tumor stage and grade of differentiation, survival after cancer therapy [35,46,47]. More interestingly, it has been shown that most CpG sites tend to become progressively hypermethylated from stage T1 through stage T3 [35].…”
Section: Dna Methylation In Hepatocellular Carcinomamentioning
confidence: 99%
“…DNMT3A seems to be the prominent responsible for the methylation of TTP promoter [45]. HCC tumors exhibit specific DNA methylation signatures associated with risk factors, tumor stage and grade of differentiation, survival after cancer therapy [35,46,47]. More interestingly, it has been shown that most CpG sites tend to become progressively hypermethylated from stage T1 through stage T3 [35].…”
Section: Dna Methylation In Hepatocellular Carcinomamentioning
confidence: 99%
“…Global hypomethylation and promoter hypermethylation have been found in hepatocarcinogenesis (14–16); therefore, the present study investigated the effects of ginsenoside Rg3 on methylation in the HepG2 human hepatocarcinoma cell line. The results showed that ginsenoside Rg3 inhibited HepG2 cell proliferation in a dose-dependent manner, induced a reduction in global DNA methylation, altered methylated cystosines in the promoter regions of specific genes, upregulated the expression of DNMT1, and downregulated the expression of DNMT3a and DNMT 3b.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of genetic events have been relevant to the development of HCC including genome instability, suppression of tumor suppressors and overexpression of oncogenes [20, 21]. Along with genetic aspects, epigenetic disruptions including changes in DNA methylation, microRNA expression have also been studied in liver cancer, and mutations or abnormal expression of epigenetic regulatory genes have been recognized [22–24]. Despite these efforts, the underlying mechanism responsible for liver carcinogenesis is largely unknown and therapeutic options remain limited.…”
Section: Introductionmentioning
confidence: 99%